COVID-19 and ST elevations–keep an open mind: a case report. Issue 6 (19th October 2020) - Kendall, Michael R; Reddy, Sridhar M; Meinke, Laura E; Acharya*, Deepak
Abstract: Background: Coronavirus disease 2019 (COVID-19) has been associated with a range of cardiovascular manifestations, including myocardial injury and thrombo-embolism. Pulmonary embolism (PE) causing anteroseptal/anterior ST elevations that mimic myocardial infarction have previously been described. This phenomenon is thought to be related to right ventricular injury from large emboli. Case summary: A 48-year-old woman with history of type 2 diabetes mellitus and hypertension presented to her local hospital with fever, cough, nausea, and dyspnoea. A test for SARS-CoV-2 was taken, and she was discharged with instructions to self-quarantine. She was subsequently notified of a positive SARS-CoV-2 result. Three days later, she re-presented with worsening dyspnoea and respiratory failure requiring intubation. On hospital Day 6, she became acutely hypoxic and hypotensive. Telemetry was noted to have ST changes, prompting ECG that revealed sinus tachycardia with prominent new ST elevations in her precordial leads. Transthoracic echocardiogram showed normal left ventricular function; however, the right ventricle was moderately dilated with positive McConnell's sign. Due to her unstable clinical state and high suspicion for PE, she was treated with tenecteplase 50 mg i.v. with complete resolution of her ST elevations and improved oxygenation. Discussion: Given the high rates of thrombo-embolic events in COVID-19 patients, PE should be in the differential diagnosis of ST elevation, particularly in younger patients with few risk factors for coronary artery disease.